OWN EDUCATIONAL STANDARD OF THE IRKUTSK NATIONAL RESEARCH TECHNICAL UNIVERSITY IN THE DIRECTION OF TRAINING "TECHNOSPHERE SAFETY” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The modern approaches to the training of students in the direction of "Techno sphere safety" are considered. It is shown that in order to improve the professional competence of students, it is possible to achieve using their own educational standards, based on which the use of the technology of the project method is recommended, as one of the most effective teaching method. The content of the standard and innovative teaching technologies used in IRNITU are considered. It is concluded that innovative teaching technologies make it possible to activate the work of students and prepare them for further professional activities at enterprises.